ABOUT TEACHING OF LANGUAGES - Eraliyeva Istatoy Oblokul (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the methodology of foreign language teaching, the history of its development as a science, the types of modern methods used in foreign language teaching methods and their use.